Interactive Radio Instruction: Twenty-Three Years of Improving Educational Quality - Bosch, Andrea (World Bank Group, 1997)
Interactive Radio Instruction (IRI) is the use of interactive lessons delivered through either radio broadcast or audiocassette. An "audio" teacher directs the lessons while classroom teachers serve as facilitators. IRI has been used in developing countries worldwide to improve the quality of education across a range of school subjects and to serve as a form of teacher development. Multiple studies of IRI consistently have shown high learning gains, decreased equity gaps, and cost-effectiveness. Twenty-three years after their initial launch, several major IRI projects continue to operate successfully. While over the years IRI has been updated in various ways, its basic structure and methodology remain largely unaltered. IRI continues to be used in projects around the world.
KerkoCite.ItemAlsoKnownAs: 2339240:86B68MJ8 2339240:UIAW5FZ6 2405685:9CTBNN9C 2405685:C59FG3QM 2405685:DTKLJRUG 2534379:SZAKK482
Keywords: ___working_potential_duplicate

Technology and Distance Education: Sharing Experience in Sindh, Pakistan - Panhwar, Farzana (1996)
Female literacy in Pakistan is among the lowest in the world. In 1981, the literacy rate was 16 percent for females, and 7.3 percent for rural women. Distance education can effect many social changes. Females would be the main beneficiaries because it is not socially acceptable for girls to leave home for education; parents do not like coeducational schools; social attitudes do not permit school education for girls on the conviction that any freedom to go out will result in sexual involvement with males; and women with low levels of education are stigmatized and accorded low social status. Both rural and urban conditions can be improved by providing women with integrated programs in hygiene, food, health, and basic and vocational education, as well as professional training in the sciences, trades, and industry. Problems with Pakistan's distance education system include the lack of opportunity for question and answer sessions; no provision to make up missed classes; absence of teachers to advise students on the use of the materials; lack of competition; lack of competent teachers; corruption and poor funding, resulting in nonavailability of materials in libraries; low standards, resulting in receipt of degrees without corresponding learning; lack of facilities for lab work in science and technical training; lack of rights to duplicate costly foreign video materials. (TD)
KerkoCite.ItemAlsoKnownAs: 2339240:QC9T2JX7 2405685:L4RKZE9D
Keywords: Access to Education; Distance Education; Educational Needs; Elementary Secondary Education; Foreign Countries; Illiteracy; Relevance (Education); Rural Women; Sex Discrimination; Social Attitudes; Vocational Education; Womens Education